Teacher readiness in implementing the independent learning curriculum in elementary schools (Education and Social Sciences Review, 2023)
The "Merdeka Belajar" Curriculum has become a fundamental cornerstone in the transformation of Indonesia's education system, with a strong emphasis on adaptive and student-centered learning. This study was conducted at Grogol 11 Elementary School with the aim of exploring educators' understanding and experiences in implementing the "Merdeka Belajar" Curriculum across the dimensions of mental readiness, physical preparedness, intelligence, and emotional aspects. A qualitative research approach utilizing interviews was employed. The research focused on two classroom groups, namely, first grade and fourth grade, representing the early and middle stages of primary education. The research findings indicate that the teaching staff at Grogol 11 Elementary School possess a profound comprehension of the "Merdeka Belajar" Curriculum concept and have undertaken thorough preparations to address emerging challenges. In terms of physical preparedness, educators in both classroom groups also demonstrated consistency in recognizing the importance of maintaining a healthy, organized, and balanced lifestyle to meet the complexities of learning demands. However, there exist variations in emotional approaches among the educators. First-grade instructors, as a transitional step from kindergarten to elementary school, place greater emphasis on a profound emotional approach to address the specific needs and challenges of children still in their youthful phase. On the other hand, fourth-grade educators tend to adopt a more personalized approach.